Correlating Physicochemical Properties of Boronic Acid-Chitosan Conjugates to Glucose Adsorption Sensitivity - Nashiru Billa; Clive J. Roberts; Jonathan C. Burley; Jonathan Aylott; Yaa Asantewaa (MDPI AG, 2012)
Phenyl boronic acid (PBA), which is known to interact with glucose, was covalently bonded to chitosan by direct reductive N-alkylation of chitosan with 4-formylphenylboronic acid (4-FPBA). Evidence of PBA bonding on chitosan was assessed by FTIR, ToF-SIMS, SEM, DSC and glucose adsorption sensitivity measurements. FTIR spectra showed strong signals at 1560 and 630 cm−1 indicating the formation of p-substituted benzene. Similarly, ToF-SIMS analyses on the conjugates registered fragments of boron ion (B−) at 11.0 m/z whose intensity increased in proportion to 4-FPBA loading. The degree to which PBA was bonded to chitosan was related to the 4-FPBA load used in the reaction (termed F1 through to F6 with increasing 4-FPBA load). Glucose adsorption sensitivity to PBA-bonded chitosan was directly related to the amount of PBA functionality within the conjugates and the physical nature of the matrices (porous or crystalline). Topographic analysis by SEM revealed that PBA-chitosan conjugates F1, F2 and F3 have porous matrices and their sensitivity to glucose adsorption was directly proportional to the degree of PBA substitution onto chitosan. Conversely, conjugates F4, F5 and F6 appeared crystalline under SEM and glucose adsorption sensitivity decreased in proportion to amount of PBA bonded to chitosan. The crystalline nature of the conjugates was confirmed by DSC, where the exothermic event related to the melting of the bonded PBA moiety, occurred at 338 °C. Thus, decreased sensitivity to glucose adsorption by the conjugates can be ascribed to the crystallinity imparted by increased content of the bonded PBA moiety, providing an optimal loading of PBA in terms of maximizing response to glucose.